The relationship between emotional intelligent and self-efficacy among employees at Wisma Persekutuan ( MITC Ayer Keroh ) Melaka / Nur Akma Abdul Aziz - Abdul Aziz, Nur Akma (Faculty of Business and Management, 2013)
This study is focuses on the relationship between emotional intelligent and self-efficacy among employees at the Wisma Persekutuan (Mitc Ayer Keroh), Melaka. This study was covered all the dimensions in emotional intelligent that effect on self-efficacy of the employee. In this chapter are includes several topics that are related to this study, which is background of study, statement of problem, research objectives, research question, significant of study, limitations of study, and definition of term for each elements that include in this study. This chapter will helps to understand and provide information about the study.Emotional intelligent plays an important role that can give effect towards selfefficacy among the employee. Several numbers of researches has been conducted to provide knowledge and information to support this statement. Based on researches that conducted by Hamid Jamshidi, Javad and Mehdi (2012), it has been stated that emotional intelligent have a significant impact on employee's self-efficacy. Besides that, according to Syed Nadeem, Dr. Aisha and Ayesha (2012), it also stated that emotional intelligent provide the positive impact on self efficacy of the staff.Emotional intelligent has five dimensions which are self-awareness, selfregulation, self-motivation, empathy and social skills, all this dimensions are based on Daniel Goleman theory (1998), and was used in this study. According to Mayer et.al (2000), and citied by Salami (2008), emotional intelligent is the individual ability to identify and express their emotions then gripping it in thinking, by understand with emotions and regulate them in individual's self and others. Based on previous researches, adopted from Salovery and Grewal (1990), citied by Jaya Amantha and Balakrishnan (2012), emotional intelligent refers to skills that enables person to monitor their emotions and those around them, distinguish between those emotions so the right decision and action can be made.